ANALISIS PENDAMPINGAN BELAJAR INTERAKTIF BERBASIS KELUARGA DALAM MENINGKATKAN MINAT BELAJAR ANAK DI LINGKUNGAN RUMAH - Ibnu Hajar; Sardi Pranata; Fadilah, Dedek Fadila Tri Julianta Tarigan; Tbn, Adam; Lara Sungam Br Ginting; Estefanie Lamtiur Gultom; Ayu Mora Simarmata; Angel Kristina Pangabean; Grace Zippora Sembiring; Nazwa Alya Fasya; Mutiara Seven Manalu; Maharani Cheche Kiranti; Fany Putri; Fadilah, Marcella Pebrina Br Tarigan; Ester Piani Telaumbanua (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze efforts to optimize children’s learning interest through interactive family-based learning assistance at home. Using a descriptive qualitative approach, data were collected through observation, semi-structured interviews, and documentation involving school-age children and parents. The findings show that interactive learning assistance, such as discussions, question-and-answer sessions, and educational games, significantly increases children’s learning interest. Children become more active, enthusiastic, and motivated, while parental involvement creates a conducive learning environment. This research contributes novelty by focusing on learning interest rather than learning outcomes, and by applying interactive family-based assistance as a strategy to strengthen children’s motivation to learn.